2005
DOI: 10.1080/03031853.2005.9523706
|View full text |Cite
|
Sign up to set email alerts
|

Wages and wage elasticities for wine and table grapes in South Africa

Abstract: A survey of 190 wine and table grape farmers in the Western Cape puts the average wage for farm labour at R928 per month in 2003 and R1123 per month in 2004. Output per worker has doubled since 1983. On farms with grape harvesters, labour is 30 per cent more productive (48 ton/worker) than on farms where wine grapes are picked by hand (37 ton/worker). At 9.75 tons per worker, table grapes are four times as labour-intensive as wine grapes. Resident men dominate the workforce on wine farms, while the resident … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
16
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 8 publications
4
16
1
Order By: Relevance
“…As noted in the Introduction, there are only two documented empirical estimates of the price (wage) elasticity of demand for farm labour in South Africa, namely -1.39 for regular farm labour in KwaZulu-Natal over the period -1978(Latt and Nieuwoudt, 1985, and -0.3 for farm labour in the Breërivier Valley of the Western Cape Province (Conradie, 2005). As comparisons for research on unskilled labour, Mazumdar and van Seventer (2002) estimated the price elasticity of demand for unskilled labour in the SA manufacturing sector as -0.9 for the 1980s and -1.15 for the 1990s.…”
Section: Demand For Farm Labour In South Africamentioning
confidence: 99%
See 1 more Smart Citation
“…As noted in the Introduction, there are only two documented empirical estimates of the price (wage) elasticity of demand for farm labour in South Africa, namely -1.39 for regular farm labour in KwaZulu-Natal over the period -1978(Latt and Nieuwoudt, 1985, and -0.3 for farm labour in the Breërivier Valley of the Western Cape Province (Conradie, 2005). As comparisons for research on unskilled labour, Mazumdar and van Seventer (2002) estimated the price elasticity of demand for unskilled labour in the SA manufacturing sector as -0.9 for the 1980s and -1.15 for the 1990s.…”
Section: Demand For Farm Labour In South Africamentioning
confidence: 99%
“…A relative increase in the cost of labour motivates farmers to replace labour with machinery, machinery contractors, labour contractors or new technologies that are labour-saving. This in turn can lead to considerable unemployment if the demand for labour is very price elastic (Lianos, 1972;Conradie, 2005), and output will fall as production costs increase (Burton et al, 1970).…”
Section: Introductionmentioning
confidence: 99%
“…Recent research by Conradie (2003 and2005), performed after the implementation of the statutory minimum wages in South Africa, found that 2 In contrast, Katz and Krueger (1992) and Card and Krueger (1995) found a positive relationship between minimum wages and employment. Dickens, Machin and Manning (1999:1) found that "minimum wages significantly compress the distribution of earnings but do not have a negative impact on employment" in the UK.…”
mentioning
confidence: 99%
“…While she found no evidence of job shedding, there was a slowdown in job creation. Conradie (2005) found that, despite an increase in the minimum wage at a rate above the inflation rate, the increase was unlikely to result in significant job losses, although seasonal workers are more at risk than permanent labour. The fact that the wine industry was doing well financially enabled farmers to pay the higher real wages without significantly cutting back on employment.…”
mentioning
confidence: 99%
See 1 more Smart Citation